INDIVIDUAL CHARACTERISTICS OF THE STUDENTS ENROLLED IN DIFFERENT TYPES OF MOTOR ACTIVITY OF PHYSICAL EDUCATION - E. M. Revenko (Russian State Vocational Pedagogical University, 2017)
The aim of this study was to examine intensity of motor and intellectual abilities and motivation for physical activity of students engaged in physical education in different sports groups.Methodology and research methods. Motor abilities of the students were assessed by measuring: hand, strength endurance, speed-power abilities, speed ability and general stamina. Assessment of general intelligence (GI) was carried out by R. Amthauer's test in the adaptation of L. A. Yasjukova. Formal-dynamic characteristics of the individuality (FDCI) were studied using the technique of FDCI feedback form proposed by V. M. Rusalov. Assessment of motivation to implement motor activity was performed using the author's questionnaire. The method of statistical information processing has allowed the author to reveal correlation communications between motor abilities and GI of first-year students.Results. Significant differences in the manifestation of the individual students' characteristics choosing practicing in different types of physical activity are experimentally established. In particular, students who chose table tennis, are inferior to the students who went in for wrestling in the manifestation of certain (power), motor skills, motivation for physical activity, but at the same time show relatively higher rates of certain intellectual abilities.Formal-dynamic traits of individuality are peculiar to students involved in table tennis, reflecting lower psychomotor activity (integrated indicator PDI - Psychomotor Development Index), in comparison with students who prefer fighting. The material presented provides a basis to argue that sports-oriented approach has some potential in the aspect of increase of efficiency of students' physical education, distinguished by individual characteristics of age specific development.Scientific novelty. Scientific findings on distinct differences in motivation to physical activity, manifestation of motor and mental abilities, and also formal and dynamic characteristics of the individuality of students who have chosen different types of physical activity have been experimentally obtained for the first time.Practical significance. The results of the present study provide the scientific rationale for the introduction of differentiated and sports-oriented approaches in the organization of physical education, taking into account individual characteristics of the age specific development of students.